انجاز لافتات توعوية حول تأثير الهاتف على الأطفال من سنتين إلى خمس سنوات - بن عطية, شهيناز (مكتبة كلية الأدب العربي والفنون, 2023)
تتلخص مذكرتنا الموسومة بعنوان " انجاز لافتات توعوية حول تأثير الهاتف على الأطفال من سنتين إلى خمسة سنوات " من خلال تصميم ملصقات تعالج خطر الهاتف وتأثيره على الطفل وتقديم بعض التوصيات للآباء للخروج من هذه الأزمة عن طريق التنبيه الصامت بواسطة اللافتة التوعوية. ومن أجل تحقيق أهداف الدراسة نجد أنفسنا معتمدين على المنهج الوصفي التحليلي لما تتطلبه طبيعة الموضوع محل الدراسة. إن استخدام الطفل للهاتف الذكي مشكلة العصر الحديث وإن اللافتات التوعوية لها التأثير الأكبر في السيطرة على هذا الخطر والحد منه من خلال التصميم التوعوي. Our memorandum entitled "Designing educational banners about the impact of the phone on children from two to five years" is summarized in designing posters that address the seriousness of the phone and its impact on the child and provide some recommendations for parents to get out of this crisis by means of a silent alert through the educational banner. In order to achieve the objectives of the study, we find ourselves relying on the analytical descriptive approach required by the nature of the subject under study. Children's use of smart phones is a problem of the modern era, and education banners have the greatest impact on controlling and reducing these risks through educational design.
Keywords: التوعوية؛ الطفل؛ الهاتف؛ الإدمان; awareness banner; child; the phone; addicted.